MANAGEMENT OF SUSTAINABLE DEVELOPMENT OF AN AGRO-INDUSTRIAL ENTERPRISE BASED ON EDUCATIONAL ACTIVITIES (USING IFODA AGRO KIMYO HIMOYA JV LLC AS AN EXAMPLE) - Uljabayev, Jahongir Rajabbayevich; Abdullayev, Anvarjon Akbaraliyevich (THE INNOVATION ECONOMY, 2026)
This article examines the role of internal corporate scientific and practical events in a company’s sustainable development management system. Based on an analysis of reports from seminars on organic fertilizers and soil restoration, the article reveals managerial and economic benefits, including improved personnel skills, improved product quality control, and reduced environmental risks.